1999
DOI: 10.1063/1.371209
|View full text |Cite
|
Sign up to set email alerts
|

Irreversibility of the antiferroelectric to ferroelectric phase transition in (Pb0.90Ba0.10)ZrO3 ceramics

Abstract: Dielectric and x-ray diffraction evidences are presented to show that the antiferroelectric to ferroelectric phase transition in (Pb0.90Ba0.10)ZrO3 ceramics is not reversible during the cooling cycle. It is shown that the stable antiferroelectric phase recovers from the metastable ferroelectric matrix on aging at room temperature. The kinetics of recovery of the antiferroelectric phase is very sluggish. It is pointed out that this type of irreversibility occurs in field induced antiferroelectric to ferroelectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 35 publications
2
37
0
Order By: Relevance
“…The phase transformation of antiferroelectric ceramic from antiferroelectric (AFE) to ferroelectric (FE) phase can be induced by a sufficiently high electric field [99][100][101][102]. This phase transformation is accompanied by a large volumetric change since the unit cell of FE phase is larger than that of AFE phase.…”
Section: Antiferroelectricsmentioning
confidence: 99%
“…The phase transformation of antiferroelectric ceramic from antiferroelectric (AFE) to ferroelectric (FE) phase can be induced by a sufficiently high electric field [99][100][101][102]. This phase transformation is accompanied by a large volumetric change since the unit cell of FE phase is larger than that of AFE phase.…”
Section: Antiferroelectricsmentioning
confidence: 99%
“…Shirane [16] investigated the phase transition behavior of Ba 2+ doping in PZ and reported that the ferroelectric intermediate phase between the AFE and PE phase for Ba 2+ concentrations was lower than x = 0.175. Pokharel and Pandey [17,18] reported that relaxor ferroelectric behavior for Ba 2+ concentrations was higher than x = 0.25. Recently, it was reported that antiferroelectric (Pb 1−x Ba x )ZrO 3 (PBZ) films, with a higher barium content of more than 45 mol%, were in paraelectric state at room temperature and possessed excellent dielectric properties comparable to (Ba,Sr)TiO 3 [6].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, most AFE ceramics are modified chemically by adding metal oxide at the A-and B-sites of the perovskite structure. The FE intermediate phase can be induced by adding Ba 2+ , Sr 2+ , and La 3+ at the Pb 2+ -site [2,[4][5][6][7]. Moreover, our recent research found that the FE intermediate phase also can be induced by adding, for example, hybrid-doped Ni 2+ /Nb 5+ , Zn 2+ /Nb 5+ , Co 2+ /Nb 5+ and Mg 2+ /W 6+ at the Zr 4+ -site [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%